NASKAH SYAIR KANJENG NABI DAN HIKAYAT NABI BERCUKUR DALAM RELASI EPIGONISTIK - Agus Sulton (POETIKA, 2013)
The Kanjeng Nabi Verses (Syair Kanjeng Nabi) is a pegon and Arabic lettered verse that tells us the story  about Prophet Muhammad when his hair was cut. The same story is also narrated in the Tale of  Shaving Prophet (Hikayat Nabi Bercukur) that was written in Jawi. Both texts tell the similar story despite their different geographical backgorund. This study enables the epigone theory as an approach to controvert the idea on act of  plagiarism between authors of  both texts then to propose the creator‘s creativity in producing texts. Identifications on texts‘ functions and themes methods, and interpretation on cultural perspectives and transcribing tradition are used in this study in order to demonstrate author‘s creativity in producing texts.Keywords: The Kanjeng Nabi Verses, The Tale of  Shaving Prophet, Epigone, text function identification,themeidentification, comparative inter pretation